Sistema de indicadores para la gestión inteligente del destino turístico Portoviejo-Ecuador - Mera Bravo, Eva Monserrate (2023)
The present investigation had as objective the design of a system of indicators to contribute to the measurement of the intelligent management of the tourist destination in Portoviejo. For this, a non-experimental exploratory investigation was maintained, given a mixed approach; said applied methodology was based on Márquez, Cuétara, Bernardo Y Mera (2020) focused on three phases, in the first one it consisted of the strategic situational diagnosis of the territory where important data regarding supply and demand were analyzed, followed by specific analyzes of the presence of the current development of the elements of an intelligent tourist destination with opinions of projects developed by authorities of the territory. In the second phase, an evaluation of the models was carried out to propose a system of indicators in Portoviejo, in order to optimize and guide guidelines for a smart city. Finally, in the third phase corresponded to the proposal of the system of indicators in which an evaluation was carried out through a specific analysis to reach the conclusion that in Portoviejo is important that the indicators that the experts have qualified with the highest score be adapted, since the system of indicators allows measuring the capacity of human talent to face the administration of the territory for a smart city. Said research contributes with designs that allow public and private entities to develop projects that help promote the tourism sector with a DTI (Smart Tourist Destination) approach.